A cohesive zone model to simulate the hydrogen embrittlement effect on a high-strength steel (Fracture and Structural Integrity, 2015)
The present work aims to model the fracture mechanical behavior of a high-strength low carbon steel, AISI 4130 operating in hydrogen contaminated environment. The study deals with the development of 2D finite element cohesive zone model (CZM) reproducing a toughness test. Along the symmetry plane over the crack path of a C(T) specimen a zero thickness layer of cohesive elements are implemented in order to simulate the crack propagation. The main feature of this kind of model is the definition of a traction-separation law (TSL) that reproduces the constitutive response of the material inside to the cohesive elements. Starting from a TSL calibrated on hydrogen non-contaminated material, the embrittlement effect is simulated by reducing the cohesive energy according to the total hydrogen content including the lattice sites (NILS) and the trapped amount. In this perspective, the proposed model consists of three steps of simulations. First step evaluates the hydrostatic pressure. It drives the initial hydrogen concentration assigned in the second step, a mass diffusion analysis, defining in this way the contribution of hydrogen moving across the interstitial lattice sites. The final stress analysis, allows getting the total hydrogen content, including the trapped amount, and evaluating the new crack initiation and propagation due to the hydrogen presence. The model is implemented in both plane strain and plane stress configurations; results are compared in the discussion. From the analyses, it resulted that hydrogen is located only into lattice sites and not in traps, and that the considered steel experiences a high hydrogen susceptibility. By the proposed procedure, the developed numerical model seems a reliable and quick tool able to estimate the mechanical behavior of steels in presence of hydrogen.
Keywords: Hydrogen embrittlement; AISI 4130 steel; Cohesive zone model